Echoes of rising tuition in students' borrowing, educational attainment, and homeownership in post-recession America - Zachary Bleemer; Meta Brown; Donghoon Lee; Katherine Strair; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2017)
State average enrollment-weighted public college tuition and fees per school year rose by 3,843 (or 81 percent) between 2001 and 2009. How are recent cohorts absorbing this surge in college costs, and what effect is it having on their post-schooling consumption? Our analysis of tuition, educational attainment, and debt patterns for nine youth cohorts across all fifty states indicates that the tuition hike accounted for 1,628, or about 30 percent, of the increase in average student debt per capita among 24-year-olds between 2003 and 2011. However, estimates indicate no meaningful response to tuition on college enrollment, years of post-high school schooling, and BA degree attainment rates. Our findings are consistent with American youth having accommodated tuition shocks not by forgoing schooling, but instead by amassing more debt. They signal an active role for the U.S. student loan system in shielding young Americans' human capital investments against shocks to (students') education costs. Further analysis demonstrates that the tuition hike and student debt increase, despite leaving higher educational attainment unchanged, can explain between 11 and 35 percent of the observed approximate eight-percentage-point decline in homeownership for 28-to-30-year-olds over 2007-15 for these same nine cohorts. The results suggest that states that increase college costs for current student cohorts can expect to see a response not through a decline in workforce skills, but instead through weaker spending and wealth accumulation among young consumers in the years to come.
Keywords: D14; E24; R21; 330; homeownership; student loans; household formation